2009
DOI: 10.1021/ja8087696
|View full text |Cite
|
Sign up to set email alerts
|

High-Nuclearity Silver Clusters Templated by Carbonates Generated from Atmospheric Carbon Dioxide Fixation

Abstract: Two high-nuclearity silver clusters have been prepared by reacting AgC(2)Bu(t) with AgBF(4) (or AgOTf) in the presence of TMEDA in air. The reaction takes up atmospheric CO(2) to give CO(3)(2-), which functions as a template for the formation of the cage compounds, whose nuclearities depend on the particular counteranions employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 163 publications
(73 citation statements)
references
References 28 publications
3
70
0
Order By: Relevance
“…17 In the presence of tetramethylethylenediamine (TMEDA), the reaction of Bu t CCAg with AgOTf in methanol in air gave [Ag 17 (CCBu t ) 14 CO 3 ]OTf in good yield. Structural determination revealed that the cation [Ag 17 (CCBu t ) 14 CO 3 ] + consists of 17 silver atoms linked by 14 alkynyl ligands, and there is a templating carbonate ion enclosed in the middle (Figure 3).…”
Section: Silver Alkynyl Clusters With Anion Templatesmentioning
confidence: 99%
“…17 In the presence of tetramethylethylenediamine (TMEDA), the reaction of Bu t CCAg with AgOTf in methanol in air gave [Ag 17 (CCBu t ) 14 CO 3 ]OTf in good yield. Structural determination revealed that the cation [Ag 17 (CCBu t ) 14 CO 3 ] + consists of 17 silver atoms linked by 14 alkynyl ligands, and there is a templating carbonate ion enclosed in the middle (Figure 3).…”
Section: Silver Alkynyl Clusters With Anion Templatesmentioning
confidence: 99%
“…19,20 Several polymetallic carbonate-containing systems have been described, showing not just interesting structural motifs but also bewildering physical properties. 20 Similarly, lanthanides are milestone entities in terms of their magnetism, and have also shown fascinating physical behaviours such as nuclear spin detection and manipulation 21,22 blocking of magnetisation at high temperatures 2326 magnetic memory in chiral systems with a non-magnetic ground state 27 and, very recently, blocking magnetisation at the atomic level.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Although some CO 3 2À -bridged or -centered complexes have been disclosedand the CO 3 2À anion in them also originated from the fixation of atmospheric carbond ioxide, [11] nanosized clusters or cluster-based infinite architectures containing Cu II ions templatedby CO 3 2À from atmospheric CO 2 are rare. From the selfassemblyp oint of view,s uch ab ig cluster as ac luster building unit (CBU) or connecting node has rarely been found in the construction of coordination architectures.…”
Section: Introductionmentioning
confidence: 99%